Attempts to understand the mechanisms of mitochondrial diseases: The reverse genetics of mouse models for mitochondrial disease - Ishikawa, Kaori; Nakada, Kazuto (Biochimica et biophysica acta. General subjects, 2021)
Mitochondrial disease is a general term for a disease caused by a decline in mitochondrial function. The pathology of this disease is extremely diverse and complex, and the mechanism of its pathogenesis is still unknown. Using mouse models that develop the disease via the same processes as in humans is the easiest path to understanding the underlying mechanism. However, creating a mouse model is extremely difficult due to the lack of technologies that enable editing of mitochondrial DNA (mtDNA). This paper outlines the complex pathogenesis of mitochondrial disease, and the difficulties in producing relevant mouse models. Then, the paper provides a detailed discussion on several mice created with mutations in mtDNA. The paper also introduces the pathology of mouse models with mutations including knockouts of nuclear genes that directly affect mitochondrial function. Several mice with mtDNA mutations and those with nuclear DNA mutations have been established. Although these models help elucidate the pathological mechanism of mitochondrial disease, they lack sufficient diversity to enable a complete understanding. Considering the variety of factors that affect the cause and mechanism of mitochondrial disease, it is necessary to account for this background diversity in mouse models as well. Mouse models are indispensable for understanding the pathological mechanism of mitochondrial disease, as well as for searching new treatments. There is a need for the creation and examination of mouse models with more diverse mutations and altered nuclear backgrounds and breeding environments. •Mouse models are indispensable in the study of the pathogenesis of mitochondrial disease.•Pathology of mitochondrial disease is diverse and complex.•Mouse models with mitochondrial and nuclear DNA mutations have been established.•These models lack sufficient diversity for a holistic study of mitochondrial diseases.•Diversity in mutations and breeding environments of mouse models is needed.